2020
DOI: 10.1002/ese3.814
|View full text |Cite
|
Sign up to set email alerts
|

Research status and analysis of stabilization mechanisms and demulsification methods of heavy oil emulsions

Abstract: Oil plays an indispensable role in the ever-increasing global energy economy. Over the past 20 years, oil demand has steadily increased from 60 to 84 million barrels per day. 1 With the explosive expansion of consumption and industry in emerging countries like China and India in the early years of the 21st century, the global average annual growth rate of demand for crude oil has grown to 3.4%. 2 The reduction in conventional oil and gas resources has led to the promotion, development, and utilization of uncon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 74 publications
(115 reference statements)
0
11
0
Order By: Relevance
“…101,103 Literature reports on the achievement of better separation efficiency in some cases when more than one demulsifier is used in the emulsion treatment. 96,104 summarizes the performance and mechanisms of action of different demulsifiers used in the treatment of oil sands and w/ o emulsions.…”
Section: Emulsion Treatment Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…101,103 Literature reports on the achievement of better separation efficiency in some cases when more than one demulsifier is used in the emulsion treatment. 96,104 summarizes the performance and mechanisms of action of different demulsifiers used in the treatment of oil sands and w/ o emulsions.…”
Section: Emulsion Treatment Methodsmentioning
confidence: 99%
“…Commercial demulsifiers used in the oil sands industry are often formulated with polymeric chains of ethylene and propylene oxides of alcohol, amino compounds, alkyl phenols, and resinous compounds with hydroxyl acceptor groups. , Propylene oxide (PO)–polymeric ethylene oxide (EO) block polymers, poly­(alkylene glycols), cardanol-based polymers, and alkylphenol resin alkoxylates are commercial emulsion breakers extensively used in the chemical treatment of the NFT process. , Literature reports on the achievement of better separation efficiency in some cases when more than one demulsifier is used in the emulsion treatment. , Table summarizes the performance and mechanisms of action of different demulsifiers used in the treatment of oil sands and w/o emulsions.…”
Section: Emulsion Treatment Methodsmentioning
confidence: 99%
“…However, the low demulsification speed of emulsified asphalt, particularly early in the process, restricts the use of emulsified asphalt mixtures (Baoju et al, 2022). The demulsification process of emulsified asphalt is determined by a range of factors, such as aggregate properties (Xu et al, 2017;Wang et al, 2021), the types and dosage of emulsified asphalt (Jin et al, 2013;Li and Wang 2014;Xiao et al, 2019;Li et al, 2021), temperature (Baoju et al, 2022), additives (Jiang et al, 2021), pH (Fajun et al, 2020), oil-water interface tension (Tao et al, 2015), and various combinations of materials and construction characteristics (Baoju et al, 2022). The aggregate typically accounts for more than 90% of the weight of the asphalt mixture (Pan et al, 2017).…”
Section: Introduction 1emulsified Asphalt Demulsificationmentioning
confidence: 99%
“…Asphaltenes are a typical component of crude oils and are known as natural surfactants. 41 The asphaltenes present in crude oil can be adsorbed on the water droplet surface and alter the interfacial property, resulting in the change in hydrate nucleation and growth in the subsea multiphase pipelines. To date, the effects of asphaltenes on hydrate formation in water-in-oil emulsions are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…However, Stoporev et al reported that asphaltenes promoted hydrate nucleation in water-in-oil emulsions for C 1 –C 3 mixed hydrate and methane hydrate. Asphaltenes are a typical component of crude oils and are known as natural surfactants . The asphaltenes present in crude oil can be adsorbed on the water droplet surface and alter the interfacial property, resulting in the change in hydrate nucleation and growth in the subsea multiphase pipelines.…”
Section: Introductionmentioning
confidence: 99%